Digital Public Relations Strategy in Building Public Trust in Madrasah in the Era of Information Disruption - Syivani Illus Shoha; Raden Bambang Sumarsono; Aan Fardani Ubaidillah (Education and Sociedad Journal, 2026)
The massive development of information technology has ushered in an era of information disruption, presenting complex challenges for Islamic educational institutions in managing their institutional image and maintaining public trust. This study aims to analyze digital communication-based Public Relations (PR) strategies in building public trust (digital trust) in madrasahs, encompassing participatory planning processes, the implementation of integrated programs, as well as evaluation and mitigation of obstacles. The research approach used is qualitative with a multi-site case study design. Data collection was conducted through in-depth interviews, field observations, and documentation at two sites. Data analysis was conducted interactively, encompassing data condensation, data presentation, and drawing conclusions. The results of the study indicate that both madrasahs successfully carried out a fundamental reconstruction of the public relations role, shifting from traditional technical-administrative functions to becoming a managerial strategic instrument. Trust within the digital community was fostered through a combination of adaptive strategies, including the participatory and inclusive formulation of communication directions, the internalization of humanistic values through a structural-cultural approach, the synchronization of social media content based on learning realities and local religious culture, and the implementation of a continuous quality improvement (CQI) based on local wisdom and the use of AI. The success of digital PR strategies in Islamic educational institutions depends heavily on the originality of the organizational culture, where a strong communication identity serves as a solid foundation for reputation in countering misinformation in this era of disruption.